2022
DOI: 10.1088/2053-1583/ac75f2
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer in a type-I van der Waals heterostructure of WSe2/PtSe2

Abstract: Energy transfer of a van der Waals heterostructure formed by monolayers of WSe2 and PtSe2 is studied by steady-state photoluminescence and time-resolved transient absorption spectroscopy. The heterostructure sample is fabricated by transferring a mechanically exfoliated WSe2 monolayer onto a PtSe2 monolayer film obtained by chemical vapor deposition. The sample is thermally annealed to improve the interface quality. Photoluminescence of the heterostructure is quenched by 4 times compared to the individual WSe2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Using a method of exfoliation for 2D materials [108,109], β-Ga 2 O 3 crystal substrate can be exfoliated into membranes or flakes due to its lattice structure with large lattice constants [110]. Instead of using a metal electrode, Chen et al [111] used graphene as the Schottky electrode to contact the β-Ga 2 O 3 membrane to fabricate a photodiode as shown in figure 8(a).…”
Section: Recent Advancesmentioning
confidence: 99%
“…Using a method of exfoliation for 2D materials [108,109], β-Ga 2 O 3 crystal substrate can be exfoliated into membranes or flakes due to its lattice structure with large lattice constants [110]. Instead of using a metal electrode, Chen et al [111] used graphene as the Schottky electrode to contact the β-Ga 2 O 3 membrane to fabricate a photodiode as shown in figure 8(a).…”
Section: Recent Advancesmentioning
confidence: 99%
“…Several studies reported that energy can be effectively transferred from a material with a large bandgap to that of a small bandgap. [28,29] A transfer of charge from the small to the large bandgap material (reversed transfer), which is energetically not favorable, has been much less observed. Such abnormal charge transfer from graphene to 2D transition metal dichalcogenides (TMD) has been reported in the type I graphene/TMD heterostructure, thanks to the effective hot carrier generation in graphene.…”
Section: Introductionmentioning
confidence: 99%
“…41 In type-I heterostructures, the band alignments of the materials cause a confinement effect both electrons and holes within the same semiconductor region, leading to the efficient recombination of the electron-hole pairs, thereby enabling stronger emission of photons or efficient charge transfer. [53][54][55] In addition, type-I heterostructure photodetectors show the presence of a carrier transmission barrier, which exists between the narrowband-gap semiconductor to the wideband-gap one. 56,57 This barrier effectively restricts the dark current and facilitates the achievement of a low dark current level.…”
Section: Introductionmentioning
confidence: 99%